2020
DOI: 10.1093/mnras/staa1866
|View full text |Cite
|
Sign up to set email alerts
|

Sustaining a warm corona in active galactic nucleus accretion discs

Abstract: Warm coronae, thick (τT = 10–20, where τT is the Thomson depth) Comptonizing regions with temperatures of ∼1 keV, are proposed to exist at the surfaces of accretion discs in active galactic nuclei (AGNs). By combining with the reflection spectrum, warm coronae may be responsible for producing the smooth soft excess seen in AGN X-ray spectra. This paper studies how a warm corona must adjust in order to sustain the soft excess through large changes in the AGN flux. Spectra from one-dimensional constant density a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 51 publications
1
18
0
Order By: Relevance
“…However, through recent radiative transfer computation in hydrostatic and radiative equilibrium, Gronkiewicz & Różańska (2020) has shown that for lower accretion rates, thermal instability should prevent the warm corona from forming. The low accretion rate system is unable to provide enough energy to sustain a warm corona (Ballantyne & Xiang 2020). It is therefore unclear whether a strong warm corona can be sustained at the low accretion rates relevant here ( m 0.015).…”
Section: Physical Properties Of the Warm Corona Modelmentioning
confidence: 90%
“…However, through recent radiative transfer computation in hydrostatic and radiative equilibrium, Gronkiewicz & Różańska (2020) has shown that for lower accretion rates, thermal instability should prevent the warm corona from forming. The low accretion rate system is unable to provide enough energy to sustain a warm corona (Ballantyne & Xiang 2020). It is therefore unclear whether a strong warm corona can be sustained at the low accretion rates relevant here ( m 0.015).…”
Section: Physical Properties Of the Warm Corona Modelmentioning
confidence: 90%
“…They are also consistent with those measured (kT warm ∼0.3-1 keV, τ warm ∼10-20) in XMM-Newton AGN samples (e.g., Porquet et al 2004;Bianchi et al 2009), and in several individual X-ray broad-band spectral analysis of AGN, such as: Mrk 509 (Petrucci et al 2013;Mehdipour et al 2015), Ark 120 (Matt et al 2014;Porquet et al 2018), HE 1143-1810(Ursini et al 2020, NGC 4593 (Middei et al 2019), Mrk 359 (Middei et al 2020), TON S180 (Matzeu et al 2020), and ESO 511-G030 (Ghosh & Laha 2021). Very recent state-of-the-art simulations have been performed showing that a warm corona with such properties can indeed exist, until sufficient internal mechanical heating is present, and that warm and hot coronae can co-exist (Petrucci et al 2018(Petrucci et al , 2020Ballantyne 2020;Ballantyne & Xiang 2020). Moreover, these authors found that no strong absorption/emission lines are formed which can well explain the absorption-free smooth soft X-ray shape observed in bare AGN, or in most other AGN when the warm absorber and any moderate relativistic reflection contributions have been removed.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Porquet et al 2004;Bianchi et al 2009) and in several individual X-ray broadband spectral analyses of AGN, such as: Mrk 509 (Petrucci et al 2013;Mehdipour et al 2015), Ark 120 (Matt et al 2014;Porquet et al 2018), HE 1143−1810 (Ursini et al 2020), NGC 4593 (Middei et al 2019), Mrk 359 (Middei et al 2020), TON S180 (Matzeu et al 2020), and ESO 511-G030 (Ghosh & Laha 2021). Very recent state-of-the-art simulations have been performed that show that a warm corona with such properties can indeed exist, until sufficient internal mechanical heating is present, and that warm and hot coronae can co-exist (Petrucci et al 2018(Petrucci et al , 2020Ballantyne 2020;Ballantyne & Xiang 2020). Moreover, these authors found that neither strong absorption nor emission lines are formed, which can explain the absorption-free smooth soft X-ray shape observed in bare AGN or in most other AGN when the warm absorber and any moderate relativistic reflection contributions have been removed.…”
Section: Summary and Discussionmentioning
confidence: 99%